Intracranial Aneurysms: Acute VS Delayed Surgery - An Analysis of 52 Cases (Bangladesh Journal of Neuroscience, 2013)
Background: Aneurysm surgery is increasing day by day in our country but the exact timing of surgery is still controversial.Objectives: The aim of this study was to determine the results of early and late surgery for aneurismal subarachnoid haemorrhage. The aim of microneurosurgical management of an aneurysm is the total occlusion of the aneurysm sac by clipping at the neck of aneurysm with preservation of flow in the parent artery and preservation of all its perforating arteries with minimal or no brain retraction.Methods: There were 52 patients included in this study among them 3 patients expired soon after the admission before surgery could take place. Hence 49 patients underwent clip surgery from July 2005 to May 2012 for 52 aneurysms because 3 patients harboured multiple aneurysms. Patients history, clinical findings, Hunt & Hess grading, Fisher grading of CT scan, preoperative & postoperative CT angiography, postoperative outcome were collected and analyzed.Results: Most of the clipping (57.14%) were done in intermediate stage (4th to 10th days), because patients usually referred from peripheral hospital on 2nd or 3rd day after the acute SAH Those who was admitted early and H&H status good, was fit to do early surgery (within 3rd day), (28.57%). Overall outcome was assessed at 3 months after SAH using the Glasgow Outcome Scale. Good outcome were observed in 40 cases among them 22 cases (42.3%) were able to return premorbid activities. Total mortality in this series were 10 cases (19.23%) which includes preoperative death while waiting for clipping -3 cases and postoperative death- 7 cases( 14.2%).Conclusion: There is no reason to postpone clipping surgery in patients who are eligible for surgery at day 5. Surgery after day 10 is associated with worse outcome. Although these studies is having high rate of mortality which can be progressively minimize by our continuous improvement of surgical skills and postoperative critical care management of aneurysm patients.Bangladesh Journal of Neuroscience 2012; Vol. 28 (1): 29-37